Fungal isolates influence the quality of Peucedanum praeruptorum Dunn - Liu, Li; Wang, Xuejun; Chen, Shaotong; Liu, Dong; Song, Cheng; Yi, Shanyong; Zhu, Fucheng; Wang, Wei; Wang, Fang; Wang, Guanglin; Song, Xiangwen; Jia, Bin; et al. (Frontiers in Plant Science, 2022)
The symbiotic relationship between beneficial microorganisms and plants plays a vital role in natural and agricultural ecosystems. Although Peucedanum praeruptorum Dunn is widely distributed, its development is greatly limited by early bolting. The reason for early bolting in P. praeruptorum remains poorly characterized. We focus on the plant related microorganisms, including endophytes and rhizosphere microorganisms, by combining the traditional isolation and culture method with metagenomic sequencing technology. We found that the OTUs of endophytes and rhizosphere microorganisms showed a positive correlation in the whole growth stage of P. praeruptorum. Meanwhile, the community diversity of endophytic and rhizosphere fungi showed an opposite change trend, and bacteria showed a similar change trend. Besides, the microbial communities differed during the pre- and post-bolting stages of P. praeruptorum. Beneficial bacterial taxa, such as Pseudomonas and Burkholderia, and fungal taxa, such as Didymella and Fusarium, were abundant in the roots in the pre-bolting stage. Further, a strain belonging to Didymella was obtained by traditional culture and was found to contain praeruptorin A, praeruptorin B, praeruptorin E. In addition, we showed that the fungus could affect its effective components when it was inoculated into P. praeruptorum. This work provided a research reference for the similar biological characteristics of perennial one-time flowering plants, such as Saposhnikovia divaricate, Angelica sinensis and Angelica dahurica.